Control and Cinema: Intolerable Poverty and the Films of Béla Tarr. Issue 1 (February 2017) - Roberts, Phillip
Abstract : In Cinema 2 Deleuze conceptualises the time-image as a cinema of infinite variation, opening the stable forms of the movement-image to an unformed and virtual outside. Five years later he would develop a similar analysis in the short 'Postscript on the Societies of Control', arguing that a new system of organisation was expanding the disciplinary formations that had reached their peak in the first part of the twentieth century. In both works Deleuze explores a world in the process of systemic deterritorialisation that has profound implications for the way that society is organised and in which the world is thought. This essay argues that the ungrounding discussed in both of these later works should be understood as part of a similar shift in the ordering of the world, where a new regime of thought has emerged. The relationship between these two concepts in Deleuze's thought has important implications with respect to our understanding of his work on cinema. I argue that this connection reveals the political dimensions of Deleuze's focus on the intolerable in the cinema books. An impoverished life, through lack of access to capital, protection and education, offers less access to life-chances and potential social transformations. I focus on cinematic depictions of poverty and powerlessness in two films by Béla Tarr to account for the significance of poverty in Deleuze's overlapping thought on cinematic creation and media control.